A Project Report on Discovery and Verification of Neighbor positions in Mobile AD HOC Networks - APARNA S, MADHUSUDHAN, and DEBRAJ SAHA (2014)
INTERNAL GUIDE: Ms. SUSHMA NARASIMHAN, MVJCE CD ONLY
Keywords: Neighbor positions in Mobile AD HOC Networks